Fatty Acid Potassium Had Beneficial Bactericidal Effects and Removed Staphylococcus aureus Biofilms while Exhibiting Reduced Cytotoxicity towards Mouse Fibroblasts and Human Keratinocytes - Kawahara, Takayoshi (Int J Mol Sci, 2019)
Wounds frequently become infected or contaminated with bacteria. Potassium oleate (C18:1K), a type of fatty acid potassium, caused >4 log colony-forming unit (CFU)/mL reductions in the numbers of Staphylococcus aureus and Escherichia coli within 10 min and a >2 log CFU/mL reduction in the number of Clostridium difficile within 1 min. C18:1K (proportion removed: 90.3%) was significantly more effective at removing Staphylococcus aureus biofilms than the synthetic surfactant detergents sodium lauryl ether sulfate (SLES) (74.8%, p < 0.01) and sodium lauryl sulfate (SLS) (78.0%, p < 0.05). In the WST (water-soluble tetrazolium) assay, mouse fibroblasts (BALB/3T3 clone A31) in C18:1K (relative viability vs. control: 102.8%) demonstrated a significantly higher viability than those in SLES (30.1%) or SLS (18.1%, p < 0.05). In a lactate dehydrogenase (LDH) leakage assay, C18:1K (relative leakage vs. control: 108.9%) was found to be associated with a significantly lower LDH leakage from mouse fibroblasts than SLES or SLS (720.6% and 523.4%, respectively; p < 0.05). Potassium oleate demonstrated bactericidal effects against various species including Staphylococcus aureus, Escherichia coli, Bacillus cereus, and Clostridium difficile; removed significantly greater amounts of Staphylococcus aureus biofilm material than SLES and SLS; and maintained fibroblast viability; therefore, it might be useful for wound cleaning and peri-wound skin.